Dry machining of brass using titanium carbonitride (TiCN) coated tool - Mohamed Ariff, Tasnim Firdaus; Kamarudin, Mohd Syahidan; Haron, Mohd Amiruddin (Trans Tech Publications Ltd., Switzerland, 2013)
Dry machining is environmentally friendly, clean and safe to be performed. Regardless of decreasing tool life due to lack of lubricants, choosing dry machining over wet machining may be a wiser choice since the cost of purchasing and disposing the cutting fluids can contribute to a higher cost. Wear rates, tool wear intensities and material removal rates (MRR) of TiCN coated tools using both dry and traditional wet machining on brass were studied with the aim in finding the optimum cutting condition from four different cutting speeds (207, 279, 372 and 498 m/min) with two sets of cutting parameters; depth of cut and feed rate (d = 0.1 mm, f = 0.2 mm/rev and d = 0.2 mm, f = 0.4 mm/rev). Temperatures at the tool-chip interface were measured to analyze the effects of temperature rise during dry machining. Cost analysis on machining cost per piece between dry and wet machining was performed. The optimum cutting condition for wet and dry machining of brass using TiCN coated cutting tool was found to be 498 m/min at d = 0.2 mm, f = 0.4 mm/rev. The tool tip temperature obtained from dry machining did not influence tool wear since the temperature rise is quite similar to the wet machining temperatures. The machining for the dry machining reduced to about 25-76% per piece when compared with wet machining.